O MERCOSUL E A REESTRUTURAÇÃO DA AGRICULTURA: AS "FILIÈRES" DE CEREAIS E A EXCLUSÃO SOCIAL - Favero, Celso Antonio e (Cadernos de Ciência & Tecnologia, 1996)
Com este trabalho, levantam-se algumas hipóteses, através das quais se visa abordar algumas das dinâmicas de reestruturação econômica e social que estão sendo operadas pela formação do MERCOSUL nos sistemas agroalimentares dos países da região. Supondo-se que o atual processo de construção de novos espaços de coerência macroeconômicos (as regiões) é acompanhado por um outro processo, o da formação de novos mesossistemas (as "filières" de produção), no nível social, vemos emergir um novo compromisso, flexível, constituído na relação de parceria. A idéia de integração social, que predominou principalmente no período do pós-guerra, vem sendo substituída por duas novas noções, que dão conta daquela flexibilização exigida, as noções de inserção e de exclusão social. MERCOSUL AND THE RESTRUCTURING OF AGRICULTURE: CEREAL PRODUCTIVE CHAINS AND SOCIAL EXCLUSION ABSTRACT With this study, we wish to raise some hypotheses, by means of which it is intended to bring up some of the dynamics of economic and social restructuring which are taking place due to the formation of Mercosul, in the agricultural food systems of the countries of the region. Presuming that the present process of construction of new spaces of macroeconomic coherence (the regions) and accompanied by another process, that of the formation of new mesosystems (the productive chains), on the social level, we are seeing emerge a new compromise, flexible, constituted on the partnership relation. The idea of social integration, which predominated principally in the post-war period, is being substituted by two new ideas, which are up to that flexibility required, the ideas of insertion and social exclusion.